On dynamics in a Keynesian model of monetary and fiscal stabilization policy mix with twin debt accumulation. (26th August 2018) - Asada, Toichiro; Demetrian, Michal; Zimka, Rudolf
Abstract: In this paper, a six‐dimensional model of flexible prices with the monetary and fiscal policy mix, describing the development of the firms' private debt, the output, the expected rate of inflation, the rate of interest, government expenditure, and government bonds are analyzed. The stress put on the "twin debt accumulation" means that in our model both private debt accumulation and the public debt (government bond) accumulation are explicitly introduced. Questions concerning the existence of limit cycles around its normal equilibrium point are investigated. The bifurcation equation is found. The formulae for the calculation of its coefficients are gained. Numerical example illustrating the results attained is presented by means of numerical simulations.